PANDEMIC IMPACT OF COVID-19 ON THE STOCK MARKET INDEX AND RETURN OF STOCK MARKET INDEX (EVENT STUDY ON STOCK MARKET INDEX IN ASEAN EXCHANGE) - Sutrisno Sutrisno; Bagus Panuntun; Fikri Irfan Adristi (Modus, 2021)
ABSTRACT The purpose of this study is to examine the impact of COVID-19 on six stock market indexes of countries listed on ASEAN Exchanges and three stock market indexes of countries listed on ASEAN Exchanges which have sectoral index of consumer products and property. The variables used in this study were the Coronavirus Disease 2019 (COVID-19) pandemic event; price and return of the six stock market indexes. The sample data in this study were measured based on the entire study period, before the date of the first confirmed case of COVID-19, and after the date of the first confirmed case of COVID-19. The population in this study is all stock market indexes of countries as well as all those that have sectoral index of consumer products and property in ASEAN Exchanges. This study was a population study conducted in the period of 2019-2020 by using the Autoregressive Distributed Lag (ARDL) Model, Autoregressive Conditional Heteroscedasticity (ARCH) Family Models, and California Managed Accounts Reports (Calmar) Ratio as the tools for analysis. The results showed that all the variables tested had a highly significant degenerating long-term relationship due to the impact of the COVID-19 pandemic; there was an ARCH or GARCH effect in all stock market indexes in ASEAN Exchanges affected by the COVID-19 pandemic; and there was a relationship between the COVID-19 pandemic event and the return on the country's stock market index and which for the consumer products and property sector in the ASEAN Exchanges with heterogeneous returns and the distribution of risk levels was inefficient. Keywords:  COVID-19; stock market index; return stock market index; ARDL Model; ARCH Family Models ABSTRAKPenelitian ini bertujuan untuk melihat dampak COVID-19 terhadap enam indeks saham di negara-negara yang terdaftar pada ASEAN Exchanges dan tiga indeks saham dari negara-negara yang terdaftar di ASEAN Exchanges yang memiliki indeks sektor konsumer dan properti. Variabel dalam penelitian ini adalah peristiwa pandemi COVID-19, harga dan return dari enam indeks saham. Data sampel diukur berdasarkan periode studi secara keseluruhan, sebelum tanggal kasus pertama COVID-19, dan sesudah tanggal kasus pertama COVID-19. Populasi dalam penelitian ini adalah semua indeks saham dari negara-negara yang terdaftar di ASEAN Exchanges dan juga mereka yang memiliki indeks sektor konsumer dan properti. Penelitian ini merupakan penelitian populasi yang dilaksanakan selama periode 2019-2020 dengan menggunakan Autoregressive Distributed Lag (ARDL) Model, Autoregressive Conditional Heteroscedasticity (ARCH) Family Models, dan California Managed Accounts Reports (Calmar) Ratio. Hasil penelitian menunjukkan bahwa semua variabel yang diuji memiliki hubungan jangka panjang yang merosot secara signifikan akibat pandemi COVID-19; terdapat efek ARCH atau GARCH pada semua indeks saham dalam ASEAN Exchanges akibat pandemi COVID-19; dan terdapat hubungan antara pandemi COVID-19 dan return indeks saham dalam negara-negara tersebut dan juga untuk sektor konsumer dan properti dalam ASEAN Exchanges dengan return yang heterogen dan distribusi tingkat risiko yang tidak efisien.Kata kunci:    COVID-19; indeks saham; return indeks saham; ARDL Model; ARCH Family Models